Dengue virus activates polyreactive, natural IgG B cells after primary and secondary infection - Balakrishnan, T.; Bela-Ong, D.B.; Toh, Y.X.; Flamand, M.; Devi, S.; Koh, M.B.; Hibberd, M.L.; Ooi, E.E.; Low, J.G.; Leo, Y.S.; Gu, F.; Fink, K. (Public Library of Science, 2011)
Background: Dengue virus is transmitted by mosquitoes and has four serotypes. Cross-protection to other serotypes lasting for a few months is observed following infection with one serotype. There is evidence that low-affinity T and/or B cells from primary infections contribute to the severe syndromes often associated with secondary dengue infections. such pronounced immune-mediated enhancement suggests a dengue-specific pattern of immune cell activation. This study investigates the acute and early convalescent B cell response leading to the generation of cross-reactive and neutralizing antibodies following dengue infection. Methodology/Principal Findings: We assayed blood samples taken from dengue patients with primary or secondary infection during acute disease and convalescence and compared them to samples from patients presenting with non-dengue related fever. Dengue induced massive early plasmablast formation, which correlated with the appearance of polyclonal, cross-reactive IgG for both primary and secondary infection. Surprisingly, the contribution of IgG to the neutralizing titer 4-7 days after fever onset was more than 50% even after primary infection. Conclusions/Significance: Poly-reactive and virus serotype cross-reactive IgG are an important component of the innate response in humans during both primary and secondary dengue infection, and ``innate specificities'' seem to constitute part of the adaptive response in dengue. While of potential importance for protection during secondary infection, cross-reactive B cells will also compete with highly neutralizing B cells and possibly interfere with their development.